Associative agriculture, the struggle for land and the community after the agrarian reform in Puno, Peru - Burneo, María Luisa (2020)
The article traces the trajectories followed by associative enterprises after the agrarian reform in Puno. It analyzes the changes in the structure of the land in light of the processes of agrarian restructuring and the formation of new peasant communities. The central argument is that the agrarian reform implemented by the Velasco government had peculiarities that should be incorporated in the reading of it as a process with regional variations. Likewise, it is argued, based on the analysis and history of two large associative companies apparatus did not make an adequate reading of the different land tenure logics of the peasant livestock families, nor of the pressure for water and land resources of the surrounding communities. The struggle for land, which arose from the expectations of thousands of communal families and from a distribution considered unequal, is one of the central axes of this text. From this perspective, the reform, more than an event that lasted from 1969 to 1975, was a process that was superimposed on previous, longer-term dynamics, which was inserted in diverse territories and in ongoing social microprocesses with which it overlapped, generating tensions and conflicts in the two following decades. In the case studied, this implied the reconfiguration of the South Andean space and the consolidation of hundreds of communities with a land tenure regime within it.